Catalytic Ester and Amide to Amine Interconversion: Nickel‐Catalyzed Decarbonylative Amination of Esters and Amides by C−O and C−C Bond Activation. (15th March 2017) - Yue, Huifeng; Guo, Lin; Liao, Hsuan‐Hung; Cai, Yunfei; Zhu, Chen; Rueping, Magnus
Abstract: An efficient nickel‐catalyzed decarbonylative amination reaction of aryl and heteroaryl esters has been achieved for the first time. The new amination protocol allows the direct interconversion of esters and amides into the corresponding amines and represents a good alternative to classical rearrangements as well as cross coupling reactions.